1991
DOI: 10.1152/ajpheart.1991.260.3.h759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of charged amphiphiles on cardiac cell contractility are mediated via effects on Ca2+ current

Abstract: Exposure of isolated adult rabbit myocytes to the negatively charged amphiphile dodecylsulfate (DDS; 10 microM) increased the contraction amplitude to 185% of control. The positively charged amphiphile dodecyltrimethylammonium (DDTMA; 10 microM) decreased the amplitude to 58%. DDS increased Ca2+ uptake by the same cells, but this uptake was partially prevented by nifedipine. DDTMA had no effect on Ca2+ uptake. Ca2+ binding to isolated sarcolemma of neonatal heart cells was increased by 10 microM DDS and, at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 0 publications
4
19
0
Order By: Relevance
“…There is evidence that alterations in membrane properties have a considerable impact on its various functions and substructures (23). In the present study we found that PFOS evidently augmented ICa ( Figure 3E) and significantly shifted the I -V curves of ICa in the negative direction ( Figures 3D and S4A), consistent with previous reports (14,24). Together with calcium imaging experiments ( Figures 4C and 4D), our findings indicated that the PFOS-induced increase in ICa was mainly mediated by L-type calcium channel.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There is evidence that alterations in membrane properties have a considerable impact on its various functions and substructures (23). In the present study we found that PFOS evidently augmented ICa ( Figure 3E) and significantly shifted the I -V curves of ICa in the negative direction ( Figures 3D and S4A), consistent with previous reports (14,24). Together with calcium imaging experiments ( Figures 4C and 4D), our findings indicated that the PFOS-induced increase in ICa was mainly mediated by L-type calcium channel.…”
Section: Discussionsupporting
confidence: 92%
“…PFOS has a sulfonic group attached to the perfluorinated chain, and PFOA has a carboxylic group. PFOS is likely to become incorporated into the lipid bilayer of the cell membrane (24), which may explain the differential effects of the two compounds on the Ca 2+ channels (Figure 3). In contrast to PFOS and PFOA, PFOC is an uncharged perfluorinated compound.…”
Section: Discussionmentioning
confidence: 99%
“…The eight-carbon-chained (C-8) OA is an anionic surfactant which can be converted to PFOA when all the hydrogen atoms in its aliphatic chain are substituted by fluorine. When comparing the effects of OA and PFOA on cultured neurons, it was found that OA showed an insignificant increase of the mPSC frequency but evidently elevated the amplitude of I Ca ( Figures 1B and 2C) indicating that the surface activities of OA (similar to the PFCs) can interfere with the physiological processes of neurons, which is in agreement with past studies on other negatively charged surfactants (13,24). The same but more observable trends were observed on neurons with PFOA ( Figures 1B and 2C).…”
Section: Pfc-induced Changes In Cultured Neuronssupporting
confidence: 90%
“…There are controversies in the literature regarding how cell swelling can modulate cardiac I Ca,L channel. For example, I Ca,L increases in neonatal rat ventricular myocytes [14] and rabbit sinoatrial node and atrial cells [12,13] , remains unaltered in canine ventricular myocytes [17] , decreases or remains unaltered in guinea-pig ventricular myocytes [10,15] . Brette et al had reported that in rat ventricular myocytes osmotic swelling decreases I Ca,L [16] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of cell swelling on cardiac I Ca,L remains controversial. For example, some studies have shown clear increases in I Ca,L [12][13][14] , while others have shown a decrease in I Ca,L [15,16] or no effect [10,17] . Some authors have even demonstrated biphasic effects on I Ca,L , an increase followed by a more sustained decrease [18] .…”
Section: Introductionmentioning
confidence: 99%